Menyingkap Misteri Pemahaman Sistem Peredaran Darah : Kehebatan Two-Tier Test Untuk Mendeteksi Miskonsepsi Di MIN SeKota Pontianak: Menyingkap Misteri Pemahaman Sistem Peredaran Darah: Kehebatan Two-Tier Test Untuk Mendeteksi Miskonsepsi Di MIN SeKota Pontianak - Angga Bayu Segara; Vidya Setyaningrum (UNIB Press, 2024)
This research focuses on the validity and reliability of the Two-Tier Test as a tool to measure misconceptions in science subjects, especially circulatory system material, among MIN students throughout Pontianak City. The research aimed to ensure that the Two-Tier Test used in this research provides valid and reliable results in analyzing student misconceptions through a reliability test. This research contributes to the development of a more specific, accurate and effective evaluation method for detecting misconceptions in science subjects, especially regarding the circulatory system. The research design adopts a Research and Development approach to create reliable measuring tools. The research subjects involved students who had studied the circulatory system material at MIN in Pontianak. Sampling was carried out using a stratified random sampling technique through a Two-Tier Test and semi-structured interviews regarding the blood circulatory system. Test validity is measured using Gregory's theory, including content, criterion and construct validity. The research results show that the Two-Tier Test has optimal validity and high reliability. A validity score of 1 indicates the instrument's accuracy in measuring the targeted attribute. The reliability of the test items, with a value of 0.71, is considered acceptable at a high level. The research conclusion shows that the Two-Tier Test is a reliable and consistent instrument for analyzing students' misconceptions, contributing to effective decision making in data analysis.